Inner strength, coping self‐efficacy and coping strategy of patients with peritoneal dialysis: A exploratory cross‐sectional study - Xuzhen Yang; Yan Shan; Yajing Gao; Hong Wang; Xue Li; Yabo Ding; Yanjun Zhang; Keke Diao; Yijia Huang (Wiley, 2024)
Abstract Aim The purpose of the study was to investigate and analyse inner strength of patients with peritoneal dialysis, explore the associations among inner strength, coping self‐efficacy (CSE) and medial coping modes. Design This was a cross‐sectional study which was conducted in nephrology departments of two affiliated hospitals of a comprehensive university in China. Convenience sampling was chosen to collect data. Methods A total of 191 patients undergoing peritoneal dialysis were recruited by convenience sampling in two hospitals. Data involved of sociodemographic and clinical materials, inner strength, CSE and medical coping modes were collected from the patients. IBM SPSS Statistics 21.0 was used to process and analyse the data. Results The averaged score of inner strength was 95.74 (SD = 13.52). The inner strength, CSE and confrontation coping had positive associations with each other. Besides, inner strength and CSE was negatively associated with acceptance-resignation coping strategy, respectively.